2022
DOI: 10.3390/pharmaceutics14122563
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Drug Repurposing Framework Predicts Repaglinide, Agomelatine and Protokylol as TRPV1 Modulators with Analgesic Activity

Abstract: Pain is one of the most common symptoms experienced by patients. The use of current analgesics is limited by low efficacy and important side effects. Transient receptor potential vanilloid-1 (TRPV1) is a non-selective cation channel, activated by capsaicin, heat, low pH or pro-inflammatory agents. Since TRPV1 is a potential target for the development of novel analgesics due to its distribution and function, we aimed to develop an in silico drug repositioning framework to predict potential TRPV1 ligands among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Currently, the vast majority of drug discoveries of TRPV1 channel modulators stem from traditional drug design methods. In the few applications of VS, Llanos (Llanos et al, 2022) and Andrei (Andrei et al, 2022) both used a strategy of drug repurposing to perform virtual screening on the DrugBank database. Our research used multiple compounds databases, and three hits were found through LBVS and SBVS methods.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the vast majority of drug discoveries of TRPV1 channel modulators stem from traditional drug design methods. In the few applications of VS, Llanos (Llanos et al, 2022) and Andrei (Andrei et al, 2022) both used a strategy of drug repurposing to perform virtual screening on the DrugBank database. Our research used multiple compounds databases, and three hits were found through LBVS and SBVS methods.…”
Section: Discussionmentioning
confidence: 99%
“…The ChEMBL database includes currently data for ~2.3 million ligands and ~15,000 targets, which were collected from published assays, scientific publications, or gathered from other databases and research institutions across the world [102,103]. Screening experiments on ion channels often exploit the ChEMBL ion channel dataset [104,105]. One can specify a particular ion channel family and subtype and obtain a list of small molecule ligands that are known to act on these targets.…”
Section: Virtual Ligand Libraries For Ion Channel Drug Discoverymentioning
confidence: 99%
“…79 Table 1 represents the progress of various TRP modulators in the clinical context. 43,[80][81][82][83][84][85][86][87][88]…”
Section: Trpm8 As a Drug Targetmentioning
confidence: 99%